Potentials of mangrove ecosystem as storage of carbon for global warming mitigation: - - Adilah Dinilhuda; Aji Ali Akbar; Jumiati; Henny Herawaty (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dinilhuda A, Akbar AA, Jumiati, Herawati H. 2020. Potential of mangrove ecosystem as carbon storage for global warming mitigation. Biodiversitas 21: 5353-5362. The mangrove ecosystem in Karimunting Bay of West Kalimantan, Indonesia is one of the conservation areas with an area of 138.2 ha. Vegetation making up of that mangrove ecosystem is dominated by Avicennia marina. The existence of mangroves has a role in carbon storage. The ability to store carbon in mangrove forest ecosystems is four times greater than in other tropical forests around the world. Mangrove stems have the greatest ability in storing carbon by up to 55.52%. The research objective was to analyze the potential for carbon storage in the fringe mangrove ecosystem which was dominated by A. marina. This research method is based on a survey of vegetation density in the field. The survey was carried out in Karimunting Bay in three parts of the bay, north, central, and south. Each part of the bay consists of two locations, namely at the front of the breakwater towards the sea and behind the breakwater towards the land. Each location consisted of a plot of 10 x 10 with five replications. The vegetation parameters measured are the types of growth forms, the mangrove ecosystem species, and the diameter and height of the trees, as well as environmental parameters (pH, temperature, and salinity). Destructive method was used on A. marina stems for estimating analysis of mangrove carbon storage in the laboratory. A. marina stem samples were used to test the carbon content with LOI (Lost on Ignition) analysis. Analysis of changes in mangrove area is based on the 2009 and 2019 landscape images. The results show that the mangrove ecosystem of Karimunting Bay has a total density of 177,480 individuals/ha. The amount of carbon storage reached 99,231  mg/ha in 2019 and predictions of total carbon storage over the last 10 years are as much as 13,717,951 tons. Deposits of carbon in fringe mangrove illustrate the carbon dioxide absorption potential of 36,390,608 tons of CO2. The amount of CO2 absorption in fringe mangrove ecosystem type plays a role in reducing greenhouse gas (GHG) emissions with a conditional target according to the Nationally Determined Contribution (NDC) in 2030 of 834 million tons of CO2 to prevent temperature increases.